Relation between waist-hip ratio and lipid profile in type 2 diabetes mellitus patients - Reddy, Pillaram Raja; Jayarama, N; Reddy, M Madhavi; Mahesh, V (Asian Journal of Medical Sciences, 2014)
Objective: To observe the relation between waist-hip ratio and lipid profile in type 2 diabetes mellitus patients. Materials and Methods: The present study was carried out at R L Jalappa Hospital attached to Sri DevaRaj Urs Medical College, Tamaka, Kolar, after a written consent from all the participants. The study includes 505 diabetic patients, in which 336 were males and 169 were females. The waist and hip circumference were measured and the ratio was taken as Waist-Hip ratio and about 5 ml of blood sample was collected and used for the estimation of serum cholesterol, triglyceride and HDL-Cholesterol levels by using standard methods. Statistical analysis was done by using independent student t test and Pearson Correlation coefficient was calculated. Results: The waist hip ratio and lipid profiles were not significantly correlated. In type 2 diabetes male patients showed higher triglycerides (177.96±100.19) with waist hip ratio>0.9, whereas female patients showed less Triglycerides (178.19±99.52) with waist hip ratio >0.8. However these differences were statistically not significant. Conclusion: Multiple anthropometric parameters are required to correlate lipid profile rather than single parameter in type 2 diabetes mellitus. Along with anthropometric measurements, lipid profile is also need be monitored in type 2 diabetics. Asian Journal of Medical Science, Volume-5(3) 2014: 51-53 http://dx.doi.org/10.3126/ajms.v5i3.9407